2011
DOI: 10.1016/j.ajpath.2011.08.021
|View full text |Cite
|
Sign up to set email alerts
|

The ADAMTS1 Protease Gene Is Required for Mammary Tumor Growth and Metastasis

Abstract: The A disintegrin and metalloprotease with thrombospondin motifs (ADAMTS) family of proteins is composed of extracellular metalloproteases, including ADAMTS1, originally identified in cachexigenic colon cancer cells. 1,2 Mice with Adamts1-null mutation exhibit urogenital defects and female infertility because of impaired remodeling of ovarian extracellular matrix (ECM), but ovarian steroid production and lactation are normal. 3-5 A range of ECM proteins have been identified as potential ADAMTS1 substrates, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 57 publications
6
76
1
9
Order By: Relevance
“…Adamts1 has been ablated in the MMTV-PyMT mouse model previously, revealing the requirement for Adamts1 during tumor metastasis (55). Importantly, that work demonstrated that Adamts1 remodels the ECM to facilitate the transition from ductal carcinoma in situ to invasive and metastatic disease.…”
Section: Discussionmentioning
confidence: 80%
“…Adamts1 has been ablated in the MMTV-PyMT mouse model previously, revealing the requirement for Adamts1 during tumor metastasis (55). Importantly, that work demonstrated that Adamts1 remodels the ECM to facilitate the transition from ductal carcinoma in situ to invasive and metastatic disease.…”
Section: Discussionmentioning
confidence: 80%
“…By extension to the role of Egfr/Ras in tumors this would be considered a tumor suppressor function. Interestingly, there is also a connection to the Egfr pathway in mammals where ADAMTS1 acts as an activator by promoting the shedding of heparin-binding EGF ligands (Liu et al 2006(Liu et al , 2009Ricciardelli et al 2011). In contrast, and in keeping with the inhibitory function of CG4096, it has also been suggested that a self-cleaved product of ADAMTS1 could act as a repressor by sequestering ligands (Liu et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ECM protease ADAMTS1 is important for ovulation [22,23] and is predominantly sequestered in its active form in the COC matrix [24]. Active ADAMTS1 has been established to play a role during invasive cancer metastasis in other tissues [25][26][27][28]. Thus, the expanded COC matrix may be conducive to invasive migration of cumulus cells.…”
Section: Introductionmentioning
confidence: 97%